Model for the Identification of Key Elements in the Management of Labor Relations and Conflict: Impact on the Internal Customer of Hotel Organizations and on Sustainable Development Goals 8 - María del Carmen Paradinas-Márquez; José Antonio Vicente-Pascual; Almudena Barrientos-Báez (Administrative Sciences, 2023)
The object of the study is to examine conflicts that occur in hotel companies, how they affect their structure, the quality of the work environment, the well-being of their workers, and their perception of the management of labor relations and conflict. For any company that wants to orient its efforts towards the fulfillment of the SDGs established in the 2030 Agenda, in this case, SDG 8 on decent work for all, it is key to understand which variables have the greatest influence on the management of labor relations and conflict. The aim is to identify those areas where they should focus their efforts to avoid organizational malaise that leads to economic and emotional costs derived from lower productivity and increased absenteeism, thus affecting their competitiveness. Information was collected to validate the objectives using a questionnaire with 57 items completed by workers with at least 5 years of experience in the sector. Using a simple linear regression, 10 key variables have been identified to explain the global satisfaction of employees, such as treatment, respect for company values, and the existence of defined processes and responsibilities.